(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
Patents are exclusive rights that can only be granted for technologies that are new, inventive and industrially applicable. Patents are assets which can help attract investment, secure licensing deals and provide market exclusivity. A patent can be maintained for a maximum of twenty years. Additive manufacturing (AM) patent applications at the European Patent Office (EPO) grew on average at a two-digit rate in the last years, much faster than the average yearly growth of patent applications at the EPO in the same period. A large share of the AM patent applications is directed to inventions in the medical and health sectors. Due to the nature of many AM inventions, there is a risk that traditional patent protection strategies do not ensure a thorough and enforceable protection of the AM invention. Recent landmark decisions of different Patent Offices and Patent Courts have acknowledged the new nature of AM inventions and provide new opportunities for effective protection of AM inventions through patents.